Genetic considerations in ecosystem restoration using native tree species. State of the World’s Forest Genetic Resources – Thematic Study. - Bozzano, M.; Jalonen, R.; Thomas, E.; Boshier, D.; Gallo, L.; Cavers, S.; Bordacs, S.; Smith, Pete; Loo, J. (Food and Agriculture Organization of the United Nations, 2014)
There is renewed interest in the use of native tree species in ecosystem restoration for their biodiversity benefits. Growing native tree species in production systems (e.g. plantation forests and subsistence agriculture) can also ensure landscape functionality and support for human livelihoods. Achieving these full benefits requires consideration of genetic aspects that are often neglected, such as suitability of germplasm to the site, quality and quantity of the genetic pool used and regeneration potential. Understanding the extent and nature of gene flow across fragmented agro-ecosystems is also crucial to successful ecosystem restoration. We review the role of genetic considerations in a wide range of ecosystem restoration activities involving trees and evaluate how different approaches take, or could take, genetic aspects into account, leading towards the identification and selection of the most appropriate methods.